Comparative activity of carbapenem testing: the COMPACT study - KORTEN, VOLKAN (OXFORD UNIV PRESS, 2011)
Objectives: Doripenem is a new carbapenem recently introduced into Europe. The COMParative Activity of Carbapenem Testing (COMPACT) study compared the susceptibility of common Gram-negative bacilli causing serious infections in hospitalized patients with doripenem, imipenem and meropenem. Methods: Gram-negative isolates (4498 total: 2171 Pseudomonas species; 1910 Enterobacteriaceae; and 417 other Gram-negative bacilli) were collected from 80 centres in 16 countries in Europe, the Middle East and Africa during 2008-09. The MICs of doripenem, imipenem and meropenem were determined using Etest methodology and broth microdilution. Susceptibility was interpreted according to CLSI, EUCAST and FDA breakpoints. Results: The MIC(90)s of doripenem, imipenem and meropenem for all isolates were 8, >= 64 and 32 mg/L, respectively. Doripenem had the lowest MIC90 for Pseudomonas species at 16 mg/L, with imipenem and meropenem values of >= 64 mg/L. Enterobacteriaceae were highly susceptible to all three carbapenems, with MIC(90)s of doripenem, imipenem and meropenem of 0.06, 0.5 and 0.12 mg/L, respectively. Other Gram-negative isolates, predominantly Acinetobacter baumannii, were resistant to all three carbapenems (MIC90 >= 64 mg/L). Susceptibility to doripenem was observed in 14.9% of isolates resistant to imipenem and/or meropenem. Conclusions: Doripenem showed excellent activity against Gram-negative isolates; generally it was more active than imipenem and at least as good as meropenem. Against Pseudomonas species, doripenem was more active than both imipenem and meropenem, with doripenem susceptibility observed for some imipenem-and/or meropenem-resistant isolates.
Keywords: doripenem; Gram-negative; imipenem; meropenem; RESISTANCE SURVEILLANCE; PSEUDOMONAS-AERUGINOSA; SUSCEPTIBILITY; DORIPENEM; PROGRAM